Gender Differences in Remission and Recovery of Schizophrenic and Schizoaffective Patients: Preliminary Results of a Prospective Cohort Study. (16th January 2012) - Carpiniello, Bernardo; Pinna, Federica; Tusconi, Massimo; Zaccheddu, Enrico; Fatteri, Francesca
Abstract : The aim of the paper was to evaluate rates of clinical remission and recovery according to gender in a cohort of chronic outpatients attending a university community mental health center who had been diagnosed with schizophrenia and schizoaffective disorder according to DSM-IV-TR. A sample of 100 consecutive outpatients (70 males and 30 females) underwent comprehensive psychiatric evaluation using the Structured Clinical Interview for Diagnosis of Axis I and II DSM-IV (SCID-I and SCID-II, Version R) and an assessment of psychopathology, social functioning, clinical severity, subjective wellbeing, and quality of life, respectively by means of PANSS (Positive and Negative Syndrome Scale), PSP (Personal and Social Performance), CGI-SCH (Clinical Global Impression—Schizophrenia scale), SWN-S (Subjective Well-being under Neuroleptics—scale), and WHOQOL (WHO Quality of Life). Rates of clinical remission and recovery according to different criteria were calculated by gender. Higher rates of clinical remission and recovery were generally observed in females than males, a result consistent with literature data. Overall findings from the paper support the hypothesis of a better outcome of the disorders in women, even in the very long term.